Material Designs and New Physical Properties in MX- and MMX-Chain Compounds - Yamashita, Masahiro; Okamoto, Hiroshi; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2013)
This is the first book to comprehensively address the recent developments in both the experimental and theoretical aspects of quasi-one-dimensional halogen-bridged mono- (MX) and binuclear metal (MMX) chain complexes of Pt, Pd and Ni. These complexes have one-dimensional electronic structures, which cause the various physical properties as well as electronic structures. In most MX-chain complexes, the Pt and Pd units are in M(II)-M(IV) mixed valence or charge density wave (CDW) states due to electron-phonon interactions, and Ni compounds are in Ni(III) averaged valence or Mott-Hubbard states due to the on-site Coulomb repulsion. More recently, Pd(III) Mott-Hubbard (MH) states have been realized in the ground state by using the chemical pressure. Pt and Pd chain complexes undergo photo-induced phase transitions from CDW to MH or metal states, and Ni chain complexes undergo photo-induced phase transitions from MH to metal states. Ni chain complexes with strong electron correlations show tremendous third-order optical nonlinearity and nonlinear electrical conductivities. They can be explained theoretically by using the extended Peierls-Hubbard model. For MMX-chain complexes, averaged valence, CDW, charge polarization, and alternating charge polarization states have been realized by using chemical modification and external stimuli, such as temperature, photo-irradiation, pressure, and water vapor. All of the electronic structures and phase transitions can be explained theoretically.
1 General Intoruduction S. Takaishi and M. Yamashita -- 2 MX-Chain Compounds -- 2.1 Pt(II)-Pt(IV) and Pd(II)-Pd(IV) Mixed-Valence Compounds H. Matsuzaki and H. Okamoto -- 2.2 Ni(III) Mott-Hubbard Compounds S. Takaishi and M. Yamashita -- 2.3 Pd(III) Mott-Hubbard Compounds S. Takaishi and M. Yamashita -- 2.4 Photoinduced Phase Transitions in MX-Chain Compounds H. Matsuzaki and H. Okamoto -- 2.5 Nonlinear Electrical Conductivity, Current Oscillation and Its Control in Halogen-Bridged Nickel(III) Compounds H. Kishida and A. Nakamura -- 2.6 Gigantic Third-Order Optical Nonlinearity of Halogen-Bridged Nickel(III) Compounds H. Kishida and H. Okamoto -- 2.7 Theory of MX-Chain Compounds K. Iwano -- 3 MMX-Chain Compounds -- 3.1 Crystal Structures and Properties of MMX-Chain Compounds Based on Dithiocarboxylato-Bridged Dinuclear Complexes M. Mitsumi -- 3.2 POP-Type MMX-Chain Compounds with Binary Counter-Cations and Vapochromism H. Iguchi, S. Takaishi and M. Yamashita -- 3.3 Photoinduced Phase Transitions in MMX-Chain Compounds H. Matsuzaki and H. Okamoto -- 3.4 Theory of MMX-Chain Compounds K. Yonemitsu.
Keywords: Chemistry; Chemistry, inorganic; Chemistry, Organic; Biochemistry; Optical materials; Chemistry; Organometallic Chemistry; Optical and Electronic Materials; Medicinal Chemistry; Inorganic Chemistry